Resuscitation of Endotheliopathy and Bleeding in Thoracic Aortic Dissections: The VIPER-OCTA Randomized Clinical Pilot Trial. (October 2018) - Stensballe, Jakob; Ulrich, Annette G.; Nilsson, Jens C.; Henriksen, Hanne H.; Olsen, Peter S.; Ostrowski, Sisse R.; Johansson, Pär I.
Abstract : BACKGROUND: Thoracic aorta dissection is an acute critical condition associated with shock-induced endotheliopathy, coagulopathy, massive bleeding, and significant morbidity and mortality. Our aim was to compare the effect of coagulation support with solvent/detergent-treated pooled plasma (OctaplasLG) versus standard fresh frozen plasma (FFP) on glycocalyx and endothelial injury, bleeding, and transfusion requirements. METHODS: Investigator-initiated, single-center, blinded, randomized clinical pilot trial of adult patients undergoing emergency surgery for thoracic aorta dissection. Patients were randomized to receive OctaplasLG or standard FFP as coagulation factor replacement related to bleeding. The primary outcome was glycocalyx and endothelial injury. Other outcomes included bleeding, transfusions and prohemostatics at 24 hours, organ failure, length of stay in the intensive care unit and in the hospital, safety, and mortality at 30 and 90 days. RESULTS: Fifty-seven patients were included to obtain 44 evaluable on the primary outcome. The OctaplasLG group displayed significantly reduced damage to the endothelial glycocalyx (syndecan-1) and reduced endothelial tight junction injury (sVE-cadherin) compared to standard FFP. In the OctaplasLG group compared to the standard FFP, days on ventilator (1 day [interquartile range, 0–1] vs 2 days [1–3]; P = .013), bleeding during surgery (2150 [1600–3087] vs 2750 [2130–6875]; P = .046), 24-hour total transfusion and platelet transfusion volume (3975 mL [2640–6828 mL] vs 6220 mL [4210–10, 245 mL]; P = .040, and 1400 mL [1050–2625 mL] vs 2450 mL [1400–3500 mL]; P = .027), and goal-directed use of prohemostatics (7/23 [30.4%] vs 13/21 [61.9%]; P = .036) were all significantly lower. Among the 57 patients randomized, 30-day mortality was 20.7% (6/29) in the OctaplasLG group and 25% (7/28) in the standard FFP group ( P = .760). No safety concern was raised. CONCLUSIONS: In this randomized, clinical pilot trial of patients undergoing emergency surgery for thoracic aorta dissections, we found that OctaplasLG reduced glycocalyx and endothelial injury, reduced bleeding, transfusions, use of prohemostatics, and time on ventilator after surgery compared to standard FFP. An adequately powered multicenter trial is warranted to confirm the clinical importance of the findings.